THE EVALUATION OF EFFECTIVE COMPLEX TREATMENT OF PATIENTS WITH GENERALIZED PARODONTITIS AND OSTEOPENIA - І.R. Yarmoshuk; M.M. Horns; L.І. Pelehan (Ukrainian Medical Stomatological Academy, 2016)
Abstract. Generalized periodontitis is a common disease. Its frequency increases with age and is characterized by inflammatory and resorption and destructive processes in the patient's periodontal tissues. The issue of surgical treatment of patients with generalized periodontitis and osteopenia is particularly topical. Numerous studies have confirmed the benefits of surgical treatment procedures using osteoplastic material to stimulate repair process of periodontal tissues. The objective of the research was to improve the effectiveness of surgical treatment of patients with generalized periodontitis and osteopenia through the combined use of osteoplastic material and antiresorptive drugs in the preoperative and postoperative periods. 93 patients at the age of 24 to 65 were examined, treated and underwent clinical observation during the research. Depending on the treatment, all patients with generalized periodontitis and osteopenia were divided into three groups, randomized by age, gender and disease duration. Patients with somatic diseases in the decompensation stage, malignant neoplasms, decompensated diabetes, and infectious diseases were excluded from the research. Patients were divided into three groups. Group I included 20 patients with generalized periodontitis and osteopenia who underwent surgical treatment according to conventional procedure. Group II included 25 patients with generalized periodontitis and osteopenia who underwent surgical treatment with local application of osteoplastic material "Easy Graft". Surgical treatment in Group III (26 patients with generalized periodontitis and osteopenia) was conducted using osteoplastic material "Easy Graft" and antiresorptive drug "Bonviva". Experimental group consisted of 22 apparently healthy individuals. All patients with generalized periodontitis and osteopenia underwent classical Cieszyński-Widmann- Neumann surgery for the periodontium of the appropriate jaw. Mouth cavity was irrigated with antiseptic solutions and anesthesia was performed with Sol. Ubistesini 4%. Two vertical incisions from the gingival margin to transitory fold of the pathological process and horizontal incisions along the gingival margin from labial and lingual (palatal) sides were performed. Modified gingival margins with the width of about 2mm were cut with scissors. Granulation tissue, dental plaque was removed. Bone edge was treated and tooth root was polished. Bone cavities were filled with "Easy Graft" material. "Easy Graft" hardened and acquired a shape of monolithic implant, but a porous one when combined with oral fluids. Mucoperiosteal flap was mobilized, cast in place, and stitched in the interdental spaces. Antiresorptive drug "Bonviva" and background drug therapy, namely Azithromycin- Astrapharm 500 mg in a dose of 1 capsule during 3 days (course dose of 1.5 g), Loratadine in a dose of 1 tablet (10 mg) once a day during 10 days and Laktovit Forte in a dose of 1 capsule 2 times a day during 10 days. The obtained results indicated that the use of osteoplastic material "Easy Graft" in the surgical treatment of patients with generalized periodontitis and osteopenia normalizes and to a lesser extent promotes the positive dynamics of indices. Combined use of osteoplastic material "Easy Graft" and antiresorptive drug "Bonviva" leads to stable process stabilization being confirmed by study indices both in early and in remote postoperative period. Regimen of surgical treatment of patients with chronic generalized periodontitis of II and III degree and osteopenia was developed combined with pharmacological therapy increasing the efficiency of surgical treatment and process stabilization, being safe and available in dentist's practice.